2017
DOI: 10.1016/j.cnsns.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of solitons in coupled nonlinear pendulums with simultaneous external and parametric excitations

Abstract: The influence of an external harmonic excitation on the intrinsic localized modes of a chain of nonlinear pendulums is numerically investigated. We show, in particular, how the existence and stability domains of solitons are modified when the coupled pendulums are simultaneously subjected to external and parametric excitations. This stabilization mechanism opens the way towards the control of the energy localization phenomena in damped nonlinear periodic lattices for efficient energy transport applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
(36 reference statements)
2
16
0
Order By: Relevance
“…The most dominant example being 1D arrays of pendulums periodically coupled with springs which have been utilized to study a variety of intriguing phenomena pertaining to coupled nonlinear oscillators. These include solitons [18], breathers [19], energy transmission in band gaps [20] and most recently helical edge states in topological insulators [21]. To this end, however, exploiting the periodicity of pendulum chains as an inherent and self-reliant mechanism for vibration absorption remains uncharted territory.…”
Section: Introductionmentioning
confidence: 99%
“…The most dominant example being 1D arrays of pendulums periodically coupled with springs which have been utilized to study a variety of intriguing phenomena pertaining to coupled nonlinear oscillators. These include solitons [18], breathers [19], energy transmission in band gaps [20] and most recently helical edge states in topological insulators [21]. To this end, however, exploiting the periodicity of pendulum chains as an inherent and self-reliant mechanism for vibration absorption remains uncharted territory.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was shown that the mass impurity in a parametrically driven, damped nonlinear coupled pendula has striking influence on the high-frequency modes [20]. Recently, The influence of adding external harmonic excitation on the intrinsic localized modes of coupled pendulums chains parametrically excited has been investigated [21]. Although the dynamics of coupled nonlinear pendulums was thoroughly investigated in the frequency and timespace domains, there is a real need to perform profound analysis of the collective dynamics of such systems in order to identify practical relations with the nonlinear energy localization phenomena in terms of modal interactions and bifurcation topologies [22].…”
Section: Introductionmentioning
confidence: 99%
“…Khomeriki and Leon [25] demonstrated numerically and experimentally the existence of three tristable stationary states. Jallouli et al [26] investigated the nonlinear dynamics of a two-dimensional array of coupled pendulums under parametric excitation and, recently [27], the energy localization phenomenon in an array of coupled pendulums under simultaneous external and parametric excitations by means of a nonlinear Schrodinger equation. The authors show that adding an external excitation increases the existence region of solitons.…”
Section: Introductionmentioning
confidence: 99%